2022
DOI: 10.1016/j.amepre.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Centers’ Performance in Cancer Screening and Prevention

Abstract: Introduction:Little is known about what clinic-level factors differentiate community health centers that achieve high performance on cancer-preventive care metrics. This study aims to describe the longitudinal trends in the delivery of 3 cancer-preventive care metrics (cervical and colorectal cancer screenings and tobacco-cessation intervention) and define and compare community health centers with high cancer-preventive care performance with those with low cancer-preventive care performance.Methods: This obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…One study found that in the CHC setting wherein health insurance is not a barrier to care, rates of colorectal and cervical cancer screening increased after implementation of the ACA; the same study found that in the CHC setting, rates of cervical cancer screening increased the most among Black patients in MES 36 . These advances may be driven in part by the ACA's preventive services provision 36–38 . Additionally, ACA Medicaid expansion was associated with improved rates of insurance coverage for patients with cancer who receive care at CHCs particularly in MES, 39 suggesting that Medicaid expansion greatly benefits patients who are socioeconomically disadvantaged 38 .…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 92%
See 1 more Smart Citation
“…One study found that in the CHC setting wherein health insurance is not a barrier to care, rates of colorectal and cervical cancer screening increased after implementation of the ACA; the same study found that in the CHC setting, rates of cervical cancer screening increased the most among Black patients in MES 36 . These advances may be driven in part by the ACA's preventive services provision 36–38 . Additionally, ACA Medicaid expansion was associated with improved rates of insurance coverage for patients with cancer who receive care at CHCs particularly in MES, 39 suggesting that Medicaid expansion greatly benefits patients who are socioeconomically disadvantaged 38 .…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 92%
“…36 These advances may be driven in part by the ACA's preventive services provision. [36][37][38] Additionally, ACA Medicaid expansion was associated with improved rates of insurance coverage for patients with cancer who receive care at CHCs particularly in MES, 39 suggesting that Medicaid expansion greatly benefits patients who are socioeconomically disadvantaged. 38 These findings are encouraging because they demonstrate that policies that facilitate access to health insurance may improve equity in cancer care.…”
mentioning
confidence: 99%
“…Many patients delayed seeking care for routine prevention and disease management due to limited in-person appointments and fear of traveling to/attending in-person visits. Since the start of the pandemic, several studies have shown a decline in receipt of preventive care [3][4][5][6] and chronic disease management. 7 Little is known about the impact of the pandemic on addressing tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…CHC settings are important to study given that they provide primary care services, including smoking cessation services, to many uninsured or Medicaid-insured patients with higher rates of smoking than the general population [ 22 , 23 ]. National quality performance data show that CHCs have high rates of assessing and treating tobacco use among their patients [ 24 , 25 ]. We tested the hypotheses that cancer survivors in ACA expansion states who reported current smoking prior to the ACA expansion would have higher odds of smoking cessation, higher odds of having a cessation medication ordered, and increased primary care utilization post-ACA compared to those in non-expansion states.…”
Section: Introductionmentioning
confidence: 99%